2022
DOI: 10.3390/insects13030303
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Alpha-Trypsin Inhibitor Heavy Chain 4 Plays an Important Role in the Development and Reproduction of Nilaparvata lugens

Abstract: The brown planthopper, Nilaparvata lugens, is a difficult-to-control insect pest affecting rice yields in Asia. As a structural component of the inter-alpha-trypsin inhibitor (ITI), the inter-alpha-trypsin inhibitor heavy chain (ITIH) has been reported to be involved in various inflammatory or malignant disorders, ovarian development, and ovulation. To reveal the function of ITIH4 in N. lugens, the gene encoding N. lugens ITIH4 (NlITIH4) was cloned and characterized. NlITIH4 contains a signal peptide, a vault … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(63 reference statements)
1
0
0
Order By: Relevance
“…aegypti female reproductive system. These results are similar to another study carried out in the brown plant hopper Nilaparvata lugens, in which an inter-alpha-trypsin inhibitor has been shown to play an important role in reproduction and ovarian development [43].…”
Section: Discussionsupporting
confidence: 91%
“…aegypti female reproductive system. These results are similar to another study carried out in the brown plant hopper Nilaparvata lugens, in which an inter-alpha-trypsin inhibitor has been shown to play an important role in reproduction and ovarian development [43].…”
Section: Discussionsupporting
confidence: 91%
“…An RNAi study in Nilaparvata lugens recently showed that injected dsRNA against inter-alpha-trypsin inhibitor heavy chain 4 (ITIH4) reduced survival, egg production, egg hatching, and delayed ovarian development. These results indicate that ITIH4 plays a vital role in development and reproduction (Ji et al, 2022). In I. typographus, inter-alpha-trypsin inhibitor heavy chain H4-like isoform X2 was downregulated in both male (-3.56 fold) and female (-3.43 fold) callow beetles compared to the sclerotized ones, suggesting that it may involve in the development and reproduction in sclerotized beetles (Figure 8B).…”
Section: Daps Involved In Beetle Digestionmentioning
confidence: 83%